Graduação em medicina: uma reflexão sobre o papel da pesquisa científica - Gomes, Luíza Ferreira (Universidade Federal de São Carlos, 2024)
The objective of this work was to reflect on the role of scientific research in personal and professional development during medical school, a reflection generated through the study "Intentional behavior of university students regarding the use of long-acting reversible contraceptives (LARC)." It analyzed the behavioral intention of UFSCar university students regarding the use of long-acting reversible contraceptives (LARC), based on the Theory of Planned Behavior (TPB). The paper begins with a reflective account followed by the complete citation of the mentioned study.
Graduation in medicine: a reflection on the role of scientific research
Keywords: Relato reflexivo; Pesquisa científica; Faculdade de medicina; Reflective account; Scientific research; Medical school; CIENCIAS DA SAUDE::MEDICINA